Effect of Green Advertising, Green Product on Purchase Decisions with Brand Image as Intervening Variable Variabel - Cervin Chaniago Chaniago; Hayati Nupus Nupus (Universitas Kuningan, 2021)
Abstract This research aims to test the influence of Green Advertising and Green Product on Purchasing Decisions by using Brand Image as an intervening variable. The sample in this research were Daihatsu Sigra users in Bogor Regency. The sampling method uses non-probability sampling. The analytical method used are, validity test, reliability test, and path test. Based on the results of analysis data can be concluded that (1) Green Advertising does not have a positive and significant effect on Purchasing Decisions, (2) Green Products have a positive and significant influence on Purchasing Decisions, Green Advertising has a positive and significant effect on Brand Image, Green Products has a positive and significant influence on Brand Image, Brand Image has a positive and significant influence on Purchasing Decisions, Brand Image is able to mediate the effect of Green Advertising on Purchasing Decisions. Keywords: Green Advertising, Green Product, Brand Image, Keputusan Pembelian